Traditional ethics of sex, life and family, sociobiology, natural law, and the dominant culture - Mario Alai (Bioethics Update, 2023)
Our society has largely rejected the traditional and religious norms about sex, family, life generation and safeguard, often considered irrational, like tradition and religion themselves, and as obstacles to individual freedom, civil rights, and a full enjoyment of human potentialities. Many of those norms, however, descend from the sociobiological nature of our species, developed by natural selection and manifested through our instincts. Therefore, we cannot be happier by ignoring them. Since people have the right to live according to their own nature, and the duty to promote the well-being of others and of themselves, many of those norms constitute a “law of nature” by which even the positive laws should abide. When disregarding traditional ethics, therefore, our society contradicts its own humanistic aspirations, failing to defend, or even violating, the rights of some of its weakest members, like women and children.